Who killed change management?. Issue 4 (7th August 2016) - Hughes, Mark
Abstract : A story is told here of an investigation into change management's apparent death, provoked by the dubious business novel Who Killed Change [Blanchard, K., J. Britt, P. Zigarmi, and J. Hoekstra. 2009. Who Killed Change? Solving the Mystery of Leading People Through Change . London: Harper Collins Publishers]. The story is told over eight chapters inviting you to investigate competing explanations for the death of change management using the structure of the story arc: stasis, trigger, quest, surprise, critical choice, climax, reversal and resolution. An annoying voice (sometimes interior monologue and at other times dialogue) of another reader keen to inform and frame your understanding of the status of change management remains ever present. The case is solved with the story's resolution providing insights into advantages of investigating over literature reviewing, the problematic/masculine nature of murder metaphors, the academic potential of story arcs and the mystery which characterises organizational change.